2009
DOI: 10.1590/s1413-70542009000100022
|View full text |Cite
|
Sign up to set email alerts
|

Rendimento e teores de macronutrientes em alface tipo americana em função de doses de nitrogênio e molibdênio em cultivo de verão

Abstract: Conduziu-se o trabalho, no município de Três Pontas, Sul de Minas Gerais, no período de outubro a dezembro de 2002, objetivando avaliar a influência de doses de nitrogênio e molibdênio no rendimento e teor de macronutrientes da alface americana (Lactuca sativa L.). Utilizou-se o delineamento de blocos ao acaso em arranjo fatorial 4 x 5, compreendendo quatro doses de nitrogênio em cobertura adicionais a dose aplicada pelo produtor de 60 kg/ha de N (0, 60, 120 e 180 kg/ha) e cinco doses de molibdênio via foliar … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
3
0
9

Year Published

2011
2011
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 10 publications
2
3
0
9
Order By: Relevance
“…Cortez et al (2009) evaluated lettuce production as a function of fertilization with calcium nitrate in a nutrient solution and concluded that increasing the doses provided better production. The mean values for the variable were similar to but lower than those observed by Resende et al (2005Resende et al ( , 2009, who used higher doses of N per ha -1 .…”
Section: Growth Variables and Yieldsupporting
confidence: 77%
“…Cortez et al (2009) evaluated lettuce production as a function of fertilization with calcium nitrate in a nutrient solution and concluded that increasing the doses provided better production. The mean values for the variable were similar to but lower than those observed by Resende et al (2005Resende et al ( , 2009, who used higher doses of N per ha -1 .…”
Section: Growth Variables and Yieldsupporting
confidence: 77%
“…Crisphead lettuce has been acquiring greater importance, mostly in the South region of Minas Gerais (RESENDE et al, 2009). This cultivar is characterized by a compact head and is ideal for the fast food market segment.…”
Section: Introductionmentioning
confidence: 99%
“…Possivelmente pela baixa dosagem do adubo orgânico utilizado no experimento. Entretanto, encontram-se na literatura vários trabalhos (BUENO, 1998;GOMES, 1998;RESENDE et al, 2009) cuja MFPA respondeu de forma quadrática à adubação química nitrogenada, mesmo com a adição de adubo orgânico.…”
Section: -----------------------Cmol C Dm -3 ------------------------unclassified
“…Fonte de variação GL quadro médio (BUENO,1998;GOMES,1998;RESENDE et al, 2009). Observam-se resultados distintos, variando em função da cultivar utilizada, frequência de fertirrigação e, possivelmente, das condições edafoclimáticas onde foram montados os experimentos.…”
Section: -----------------------Cmol C Dm -3 ------------------------unclassified
See 1 more Smart Citation